Magic Realism in Hiligaynon Urban Legends - Tribunal, Ruth (JPAIR Multidisciplinary Research, 2015)
In the modern time, urban legends become unique and valuable stories in the community. These are living people’s testimony about their experiences with mix magical and mundane elements in an overall context of realistic narrations. The primary concern of this paper was to analyze and evaluate the elements of magic realism in Hiligaynon urban legends. The study is a critical literary analysis conducted within the context of descriptive research. The tool used in critiquing the Hiligaynon urban legends was Magic realism. The result of the study showed that Hiligaynon urban legends have the elements of Magic Realism, such as Fantastical elements, Real-world setting, Plenitude, Hybridity, and Mystery. Also, the culture, belief and tradition of the region shaped the elements of magic realism in Hiligaynon urban legends. These could be evident in the plots, characters, themes and settings of the stories. The study concludes that there is a genre of magical or unreal elements in every Hiligaynon urban legend. The study recommends that the school may use Hiligaynon urban legends as materials in teaching regional literature for the students to recognize the beauty of their oral tradition.